DETERMINANTS OF INCLUSIVE GROWTH IN G20 COUNTRIES WITH GENDER INEQUALITY INDEX AS A MODERATING VARIABLE - Putra, Aji Binawan; Muhdir, Ibnu (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: Inclusive growth involves substantial discussions aimed at fostering inclusivity in global society. This research is important because it seeks to explain inclusive growth driven by investment, government spending, and trade openness, with the gender inequality index as a moderating variable in G20 countries over the period from 2007 to 2021. Methods: This research is a quantitative study using Ordinary Least Squares (OLS) regression and Moderated Regression Analysis methods (MRA). Results: The findings from the three variables included in this study indicate that two variables can influence inclusive growth, namely government spending and trade openness, while the investment variable does not affect inclusive growth. Conclusion and suggestion: This is due to the fact that G20 countries have not been able to realize the impact of investment rates on inclusive growth. In addition, the gender inequality index is capable of moderating the influence of government spending on inclusive growth. Thus, in creating inclusive growth, the government must be able to allocate its funds wisely and equitably to all elements of society, both men and women.